2006
DOI: 10.4028/www.scientific.net/msf.519-521.1675
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Grain Refinement and Cooling Rate on the Hot Tearing of Wrought Aluminium Alloys

Abstract: Using modifications to the Rappaz-Drezet-Gremaud hot tearing model, and using empirical equations developed for grain size and dendrite arm spacing (DAS) on the addition of grain refiner for a range of cooling rates, the effect of grain refinement and cooling rate on hot tearing susceptibility has been analysed. It was found that grain refinement decreased the grain size and made the grain morphology more globular. Therefore refining the grain size of an equiaxed dendritic grain decreased the hot tearing susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 9 publications
1
50
0
Order By: Relevance
“…However, once a given alloy is 'sufficiently' inoculated (as discussed in section 4.2), further additions are not important with respect to the decrease in grain size and the alloy becomes less sensitive to cooling rate. Increasing the refiner amount may, however, influence the grain morphology [65,66] as discussed below.…”
Section: Grain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…However, once a given alloy is 'sufficiently' inoculated (as discussed in section 4.2), further additions are not important with respect to the decrease in grain size and the alloy becomes less sensitive to cooling rate. Increasing the refiner amount may, however, influence the grain morphology [65,66] as discussed below.…”
Section: Grain Sizementioning
confidence: 99%
“…On the other hand, there are reports that the formation of very fine globular grains can increase the hot tearing susceptibility due to the limited permeability of the mushy zone [65,66].…”
Section: Grain Sizementioning
confidence: 99%
“…Experimentally, it has been found that although grain refinement generally increases hot tearing resistance, grain refinement below 100 lm actually increases hot tearing tendency in wrought aluminum alloys during casting. [31] Although the hot tearing strain predictions are not all that different among the three cases A, D, and E, the challenge in this area of research has been to quantitatively predict hot tearing formation in an industrially cast component. As shown in Figures 6 and 7, the inclusion of key details such as semisolid constitutive behavior that is a function of grain size is needed to capture both the macroscale and microscale aspects of this defect.…”
Section: B Effect Of Microstructure Variationsmentioning
confidence: 99%
“…4(b) due to the presence of Ti segregation when the final grain morphology is globular or spherical. Figure 5(a) compiles data 31) for the grain size and the SDAS with cooling rate for each of the alloys. The grain size data is for the alloys with only an addition of 0.005 mass% Ti as Al-3Ti-1B master alloy, i.e.…”
Section: þmentioning
confidence: 99%